Recurrent Vertigo of Childhood: Clinical features and prognosis - Dunker, Konstanze; Schnabel, Lutz; Grill, Eva; Filippopulos, Filipp Maximilian; Huppert, Doreen (Frontiers in Neurology, 2022)
Introduction “Recurrent Vertigo of Childhood” (RVC) has recently replaced the term “Benign Paroxysmal Vertigo of Childhood” and was defined as recurrent spells of vertigo without evidence of a vestibular migraine of childhood (VMC). RVC and VMC are considered the most frequent causes of vertigo and dizziness in children below 18 years of age. Diagnosis might be challenging since clinical features of RVC and VMC may overlap. Objective This study aims to characterize clinical and instrument-based findings in patients with RVC and to evaluate the course of the disorder. Methods We prospectively collected clinical and instrument-based data of children/adolescents younger than 18 years, who presented at the German Center for Vertigo and Balance Disorders (DSGZ) at the LMU University Hospital in Munich. All patients underwent a comprehensive neurological, ocular motor, vestibular and cochlear examination. Furthermore, findings from follow-up examinations were analyzed. Results Overall 42 children (24 male and 18 female) with RVC were included in the study. The mean age at diagnosis was 7 ± 3.6 years with a mean onset of symptoms at the age of 5.6 ± 3.4 years. Attack duration ranged between 1 min and 4 h. The most common accompanying symptoms included nausea, vomiting, expression of fear, and falls. Non-migrainous headaches were reported by 11 patients during initial presentation, 7 of whom were later diagnosed with migraine. Female patients showed a higher age at symptom onset, a higher attack frequency, and attack duration. Eleven of the 24 patients seen at a 3.5 year follow-up reported a complete cessation of attacks. Patients still experiencing vertigo attacks had a significantly reduced attack frequency, especially those who implemented at least one prophylactic measure. Conclusion A precise characterization of symptoms is essential for diagnosing children with RVC. Age at symptom onset does not exceed the age of 12. Gender-specific differences should be considered and may further support the evidence of an association with migraine. The disease course of RVC is benign, nevertheless implementing prophylactic measures such as regular exercise, increased fluid intake, sleep hygiene, and relaxation exercises, can improve attack frequency.